Writing Workshop: AI-powered Academic Assistant for Research and Publication (ChatGPT + Scite) - Ahmad, Siti Noor Dina; Andu, Yusrina; Jaafar, Zuraida; Yaacob, Nurul Aityqah; Othman, Norlida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
On 28 August 2025, the Faculty of Computer and Mathematical Sciences (FSKM) at UiTM Cawangan Negeri Sembilan, Kuala Pilah Campus, held the AI Powered Academic Assistant for Research and Publication (ChatGPT + Scite) Workshop at the Smart Classroom, bringing together 18 lecturers from FSKM and the Faculty of Applied Sciences (FSG). Participants from diverse fields such as biology, chemistry, and food technology explored the use of AI tools to enhance scholarly writing and research, highlighting the wide applicability of AI in academic support across disciplines.